Functional and epigenetic phenotypes of humans and mice with DNMT3A Overgrowth Syndrome - Amanda M. Smith (Nature Portfolio, 2021)
Germline mutations in the DNMT3A gene can cause an overgrowth syndrome associated with behavioural and hematopoietic phenotypes. Here the authors describe a mouse model of this syndrome that recapitulates many of these features, including conserved alterations in DNA methylation in the blood cells of both species.